Rapid Response Systems as Secondary Responders to In-Hospital Clinical Deterioration: A Four-Year Observational Study - Yoan Devina; Sidharta Kusuma Manggala; Andi Ade Wijaya Ramlan; Dita Aditianingsih; Riyadh Firdaus; Arief Cahyadi; Aino Nindya Auerkari; Noor Hafidz; Luther Holan Parasian; Adhrie Sugiarto; Aivi Mujono; Avisa Cetta Cresma (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2026)
Background: In-hospital cardiac arrest (IHCA) is a major cause of preventable inpatient mortality, especially in low- and middle-income countries (LMICs) where rapid response systems (RRS) are still developing. Evidence regarding RRS performance in Indonesia is limited. This study evaluated the performance and operational challenges of an institutional RRS over four years at a large tertiary referral hospital in Jakarta.Objective: This study aimed to determine the proportion of immediate survival following RRS activation and to investigate secondary outcomes, including the association between activation indications and mortality, and system-level barriers.Methods: This retrospective observational cohort study included all inpatient RRS activations at Cipto Mangunkusumo National General Hospital (RSCM), Jakarta, Indonesia, from January 1, 2021, to December 31, 2024. Data from the hospital’s RRS registry were analyzed for activation triggers, interventions, immediate outcomes, and operational issues.Results: Among 246,367 inpatient admissions, there were 5,900 eligible inpatient RRS activations, yielding an activation rate of 23.9 per 1,000 admissions. Immediate survival occurred in 4,763 (80.7%) events, while 1,137 (19.3%) patients did not survive. Cardiac arrest (8.0%) and respiratory arrest (6.5%) were the strongest predictors of non-survival odds ratio (OR) 48.17 and 27.13 vs. red early warning score (EWS) reference, both p<0.001). Most activations occurred out of hours (63.0%), and mortality was significantly higher (71.3% vs. 61.1%; p < 0.001). The most frequent single-parameter triggers were oxygen saturation ≤90% (38.5%) and sudden deterioration of consciousness (15.8%). Mismatched activations, where the patient’s condition upon team arrival differed from the activation indicationwere strongly associated with higher mortality (OR 17.3, 95% confidence interval (CI) 14.3–20.2, p<0.001).Conclusion: The institutional RRS demonstrated a moderate activation rate and favorable immediate survival compared with similar LMIC settings. However, outcomes were influenced by delayed recognition, out-of-hours activation, and limited critical-care capacity. Strengthening early-escalation culture, monitoring afferent-limb failure (ALF), expanding nighttime coverage, and increasing intensive care unit (ICU) capacity are essential to enhance RRS effectiveness and reduce preventable in-hospital mortality in resource-limited settings.